SÄRAT PANGRACUTAN SUNTINGAN TEKS DAN TERJEMAHAN - , F GALIH ADI UTAMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis is the result of philological study of the SÄrat Pangracutan text that Pura Pakualaman Yogyakarta collection with code of collection 0125/PP/73. This study presents the text editing and translation from Javanese to Indonesian with the purpose of facilitating the reader in understanding the content of the text. General content of the SÄrat Pangracutan text describes about kalÄpasan and an explanation about condition of human bodies, naming type of death, manÄkung ordinance, also spells to release the spirit. Stages of research presentation includes an inventory of manuscripts